(3GdJPcQI GdUaOjIs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3eHJhQ,hChd GdehLhO ajg (B: (3JHGYg ceG jNQL GdSge HbhI ef efLfjbg MhdgG eYGKQ CMLGQ cCfgG bHhQ HYKQJ , ChLHGd JaWQJ HjfgG eNGFV dGHd eZGFV cGfgG HMGQ aLQJ s
(3BNQgG (B:s
(3hCf jfaYg HGdGfJeGA EPG CdReJg GdOfjG WGFQg ai jOg hCdReJg GdBNQI WGFQg ai Yfbg Bejf hMSHfG Gddg hcai s
(3GfXQ GdLRA GdChd HGdCQbGe (B130-133-(3GOHs
(3LeY ajgG GdcKjQ ef fhGOQ GdCTYGQ hGdWGFa GdBOGH fTQkG hfXekGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3GdLRA (B1 - (3U (B388 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B166 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs